Unlocking Trade Credit Opportunities and Working Capital Efficiency through ESG Disclosure - Nidhin Mathath; Vinod Kumar (Australasian Accounting, Business and Finance Journal, 2024)
This paper explores the impact of firms’ ESG performance on their trade credit financing and working capital efficiency, utilizing a sample of 586 Indian firms listed on the National Stock Exchange (NSE) from 2015 to 2022. The study offers robust evidence supporting the positive connection between superior ESG disclosure and trade credit, as well as the negative link between ESG disclosure and the cash conversion cycle. These findings underscore the role of ESG disclosure in increasing suppliers’ willingness to extend trade credit and facilitating efficient working capital management practices. The result shows that improved ESG disclosure practices increase payable turnover days and reduce both inventory turnover and receivable turnover days, reflecting the enhanced operational efficiency and market power of the firm.
Keywords: ESG disclosure; Trade credit; Working capital efficiency; Market power